Towards the realisation of the right to a fair hearing of child offenders in post-conflict Sierra Leone - Akonumbo, Atangcho Nji (University of Pretoria, 2006)
Prepared under the supervision of Dr. Atangcho Nji Akonumbo at the Faculte de Sciences Sociales et de Gestion, Universite Catholique d'Afrique Centrale, Yaounde